A preparation method for sodium ion battery layered cathode material synthesized based on MOF high entropy strategy

Through the preparation method of sodium ion battery layered positive electrode material synthesized based on MOF high entropy strategy, the problems of slow air sensitivity and Na diffusion kinetics of O3 type materials are solved, and the structural stability and electrochemical performance of the material are improved.

CN119118224BActive Publication Date: 2025-03-25HAINAN TROPICAL OCEAN UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411587619.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-25
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The layered cathode material of O3-type sodium ion battery limits its practical application prospects due to its inherent air sensitivity and slow Na diffusion kinetics.

Method used

The precursor was prepared by a metal-organic framework and calcined at high temperature to enhance structural stability and electrochemical properties.

Benefits of technology

It improves the structural stability and electrochemical properties of the material, enhances the comparative capacity, solves the structural collapse problem of MOF materials in circulation, and improves the air sensitivity and dynamic performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118224B_ABST
    Figure CN119118224B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a sodium ion battery layered positive electrode material synthesized based on a MOF high entropy strategy, belonging to the field of electrochemistry, and comprising the following steps: preparing a precursor based on a metal-organic framework, wherein the precursor comprises: Ni-MOFs and Ni / Mn-MOFs; mixing the precursor with Na2CO3, MnO2, CuO, Fe2O3, TiO2, and MgO to obtain a mixed precursor; and calcining the mixed precursor at a high temperature to obtain a sodium ion battery layered positive electrode material. The invention solves the structural collapse of MOF materials in circulation and enhances the electrochemical performance and structural stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical technology, and in particular relates to a method for preparing a sodium ion battery layered positive electrode material synthesized based on a MOF high entropy strategy. Background Art

[0002] Sodium-ion batteries (SIBs) have become a promising new energy material, not only because of their low raw material cost and large reserves, but also because of their higher safety and superior high / low temperature reliability compared to the most advanced lithium-ion batteries. O3-type materials can provide higher specific capacity because there is enough Na in the initial framework. + reservoir, which makes them attractive when paired with Na-free anodes. However, their practical application prospects are limited by two key drawbacks, namely intrinsic air sensitivity and sluggish Na diffusion kinetics. When O3 materials are exposed to air, some active Na escapes from the lattice to the surface, accompanied by the formation of Na-deficient phases and oxidation of transition metal ions in the bulk. Therefore, finding a simple and general strategy to resolve this contradiction and achieve simultaneous improvements in air sensitivity and kinetics is crucial to promote the commercial application of O3-based Na-based layered oxide cathodes. Summary of the invention

[0003] In order to solve the above technical problems, the present invention proposes a method for preparing a layered positive electrode material for a sodium ion battery synthesized based on a MOF high entropy strategy to solve the problems existing in the above-mentioned prior art.

[0004] To achieve the above object, the present invention provides a method for preparing a sodium ion battery layered cathode material synthesized based on a MOF high entropy strategy, comprising:

[0005] Preparing a precursor based on a metal-organic framework, wherein the precursor includes: Ni-MOFs and Ni / Mn-MOFs;

[0006] The precursor is mixed with Na 2 CO 3 、MnO 2 , CuO, Fe 2 O 3 、TiO 2 , and MgO to obtain a mixed precursor;

[0007] The mixed precursor is calcined at high temperature to obtain a layered positive electrode material for a sodium ion battery.

[0008] Optionally, the process of preparing Ni-MOFs comprises:

[0009] Prepare a first raw material, the first raw material comprising: Ni(NO 3 )2 6H 2 O, PTA and DMF;

[0010] At room temperature, 0.4984 g of PTA was added to 15 ml of DMF to obtain a first PTA solution; and 0.8724 g of Ni(NO 3 ) 2 6H 2 O to obtain Ni(NO 3 ) 2 6H 2 O solution;

[0011] The first PTA solution and Ni(NO 3 ) 2 6H 2 After the O solutions were stirred, the stirred first PTA solution was poured into the Ni(NO 3 ) 2 6H 2 O solution and stirred to obtain a transparent turquoise mixed solution;

[0012] Pour the transparent cyan mixed solution into the inner lining of a reactor at 120° for reaction for 12 hours, and cool to room temperature to obtain a cooled mixed solution;

[0013] The cooled mixed solution was centrifuged, and during the centrifugation, it was repeatedly washed and centrifuged three times with anhydrous ethanol, and the solution after washing and centrifugation was dried to obtain Ni-MOFs.

[0014] Optionally, the process of preparing Ni / Mn-MOFs includes:

[0015] Prepare a second raw material, the second raw material comprising: Ni(NO) 3 6H 2 O、Mn(NO) 3 ·4H 2 O, PTA and DMF solvents;

[0016] At room temperature, 0.996 g of PTA was added to 30 ml of DMF to obtain a second PTA solution; and 0.8724 g of Ni(NO 3 ) 2 6H 2 O and 0.753 g of Mn(NO) 3 ·4H 2 O to obtain a Ni / Mn mixed solution;

[0017] After stirring the second PTA solution and the Ni / Mn mixed solution respectively, pouring the stirred second PTA solution into the Ni / Mn mixed solution and stirring to obtain a transparent brown mixed solution;

[0018] Pour the transparent brown mixed solution into the inner lining of a reactor at 120° for reaction for 12 hours, and cool to room temperature to obtain a cooled mixed solution;

[0019] The cooled mixed solution was centrifuged, and during the centrifugation, it was repeatedly washed and centrifuged three times with anhydrous ethanol, and the solution after washing and centrifugation was dried to obtain Ni / Mn-MOFs.

[0020] Optionally, the mixed precursor is calcined at high temperature to obtain a sodium ion battery layered positive electrode material, and the sodium ion battery layered positive electrode material comprises:

[0021] High Ni NaNi 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 and

[0022] NaNi with high Ni / Mn 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 .

[0023] Alternatively, prepare NaNi with high Ni content 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 The process includes:

[0024] Using the Ni-MOFs as a nickel source precursor;

[0025] The nickel source precursor, 0.334 g of Na 2 CO 3 , 0.261 g of MnO 2 , 0.0795g CuO, 0.0798g Fe 2 O 3 , 0.0798 g TiO 2 and 0.04 g of MgO were placed in an agate mortar and ground to obtain a gray powder;

[0026] The gray powder is placed in a porcelain boat, and the gray powder is calcined at high temperature to obtain NaNi with high Ni content. 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 .

[0027] Alternatively, NaNi with high Ni / Mn is prepared 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 The process includes:

[0028] Using the Ni / Mn-MOFs as nickel source and manganese source precursors;

[0029] The nickel source and manganese source precursors, 0.334 g of Na 2 CO 3 , 0.0795g CuO, 0.0798g Fe 2 O 3 , 0.0798 g TiO 2 and 0.04 g of MgO were placed in an agate mortar and ground to obtain a gray powder;

[0030] The gray powder is placed in a porcelain boat, and the gray powder is calcined at high temperature to obtain NaNi with high Ni / Mn 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 .

[0031] Optionally, the conditions for high-temperature calcination of the gray powder include:

[0032] The temperature was raised to 500°C at a rate of 5°C per minute and calcined for 5 hours. The temperature was further raised to 900°C at a rate of 5°C per minute and calcined for 15 hours. Finally, the mixture was cooled to room temperature.

[0033] Compared with the prior art, the present invention has the following advantages and technical effects:

[0034] The present invention first uses a solvent-thermal method to bridge Ni single metal, Ni and Mn bimetallic ions with an organic framework of terephthalic acid as a skeleton, and synthesizes a unique organic framework for use in the electrode material of a sodium ion battery. Then, the MOF is in situ calcined at high temperature to enhance the structural stability of the process while increasing the specific capacity of the battery. This solves the structural collapse of the MOF material during the cycle and enhances the electrochemical performance and structural stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0036] Figure 1 Standard cards for general high, Ni high, Ni / Mn high and their raw materials according to the embodiments of the present invention;

[0037] Figure 2 The first charge and discharge curves of ordinary high, Ni high, and Ni / Mn high at a current density of 0.1C in the embodiment of the present invention;

[0038] Figure 3 The cycle performance of ordinary high, Ni high, and Ni / Mn high in the embodiments of the present invention at a current density of 0.1C;

[0039] Figure 4 The rate performance of general high, Ni high, and Ni / Mn high of the embodiments of the present invention;

[0040] Figure 5 The Nyquist diagrams of general high, Ni high, and Ni / Mn high of the embodiments of the present invention;

[0041] Figure 6 A flow chart of the preparation of the positive electrode material according to an embodiment of the present invention;

[0042] Figure 7 The figure shows the laboratory preparation process of the positive electrode material according to the embodiment of the present invention. DETAILED DESCRIPTION

[0043] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0044] It should be noted that the steps shown in the flowcharts of the accompanying drawings can be executed in a computer system such as a set of computer executable instructions, and that, although a logical order is shown in the flowcharts, in some cases, the steps shown or described can be executed in an order different from that shown here.

[0045] Embodiment 1

[0046] Metal-organic frameworks (MOFs) are a group of porous materials with high crystallinity that have been widely used as synthetic metal oxides mainly due to their unique structural properties, including large surface area, well-defined pore structure, presence of metal active sites, and channel-based structure.

[0047] High entropy oxides (HEOs) have been introduced as a new concept to develop advanced materials with unique properties that cannot be achieved by traditional materials with only one or a few dominant elements. HEOs represent multi-element metal systems that can crystallize in a single phase, where different systems can adopt different crystal structures, including single-phase rock salt, spinel, and perovskite structures. Typically, five or more main elements share equiatomic sites in HEO, which can stabilize the solid solution state. Due to the extremely complex composition of these materials, they usually exhibit excellent properties such as high fracture toughness, high strength, good high and low temperature properties, and good energy storage properties. Therefore, in this prepared high entropy cathode, six different elements were used to share the octahedral TM sites in the O3-NaTMO2 system, among which Ni 2+ , Cu 2+ and Fe 3+ Expected to provide charge compensation for capacity. Mg 2+ and Ti 4+ Can be found in Na + Stabilize the entire structure during the extraction / insertion process. Mn4 + It can promote the formation of its rich structure.

[0048] To address the above problems, the electrochemical performance of sodium-ion batteries is improved by combining porous MOF materials with high entropy strategies. MOF materials themselves have large specific surface areas and high porosity. The large specific surface area enables the electrode material to fully contact the electrolyte, while the high porosity can accelerate the transmission of sodium ions. Six different elements are used to share the octahedral TM site Ni in the O3-NaTMO2 system. 2+ , Cu 2+ and Fe 3+ Expected to provide charge compensation for capacity. Mg 2+ and Ti 4+ It can stabilize the entire structure during the Na-(de) intercalation process. 4+ It can enrich its structure.

[0049] This embodiment provides a method for preparing a sodium ion battery layered positive electrode material based on MOF high entropy strategy synthesis, comprising the following steps: preparing a precursor based on a metal-organic framework, wherein the precursor includes: Ni-MOFs and Ni / Mn-MOFs; mixing the precursor with Na 2CO 3 、MnO 2 , CuO, Fe 2 O 3 、TiO 2 , MgO to obtain a mixed precursor; the mixed precursor is calcined at high temperature to obtain a layered positive electrode material for a sodium ion battery. The preparation process is as follows: Figure 6 and Figure 7 shown.

[0050] Preparation of Ni-MOFs

[0051] First raw material: Ni(NO 3 ) 2 6H 2 O(AR), PTA (AR), DMF solvent (AR)

[0052] Preparation method: At room temperature, add 0.4984g of PTA to 15ml of DMF and 0.8724g of Ni(NO 3 ) 2 6H 2 O, stirred for 5 min to fully dissolve, then slowly poured the PTA solution into the Ni(NO 3 ) 2 6H 2 O solution, stirring continuously at 350 rpm for 30 min until the solution turns transparent turquoise. Then pour the mixed solution into the reactor liner and react at 120° for 12 h. After cooling to room temperature, centrifuge the solution at 8500 rpm for 3 min, wash repeatedly with anhydrous ethanol and centrifuge for 3 times, and then dry in an 80°C forced air drying oven for 6 h to obtain Ni-MOFs.

[0053] Preparation of Ni / Mn-MOFs

[0054] Second raw material: Ni(NO 3 ) 2 6H 2 O(AR),Mn(NO) 3 ·4H 2 O(AR), PTA(AR), DMF solvent(AR)

[0055] Preparation method: At room temperature, add 0.996g of PTA to 30ml of DMF and 0.8724g of Ni(NO 3 ) 2 6H 2 O and 0.753 g of Mn(NO) 3 ·4H 2O were stirred for 5 minutes to fully dissolve, and then the PTA solution was slowly poured into the mixed solution containing Ni / Mn, and stirred at 350 rpm for 30 minutes until the solution turned transparent brown. Then the mixed solution was poured into the lining of the reactor and reacted at 120° for 12 hours. After the temperature cooled to room temperature, the solution was centrifuged at 8500 rpm for 3 minutes, during which it was repeatedly washed with anhydrous ethanol and centrifuged 3 times, and then placed in an 80°C forced air drying oven for 6 hours to obtain Ni / Mn-MOFs.

[0056] NeNi 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 Preparation (General High)

[0057] Raw material: Na 2 CO 3 , NiO, MnO 2 , CuO, Fe 2 O 3 、TiO 2 MgO

[0058] Preparation method: weigh 0.334g Na according to the stoichiometric ratio 2 CO 3 (5% excess to make up for the lack of sodium in high temperature calcination), 0.0224g NiO, 0.261g MnO 2 , 0.0795g CuO, 0.0798g Fe 2 O 3 , 0.0798 g TiO 2 , 0.04g MgO. After the above raw materials are fully ground in an agate mortar for 1 hour, the gray powder is dispersed into a porcelain boat, and the porcelain boat is placed in a simple position in a tube furnace, and the temperature is increased to 500°C at a rate of 5°C per minute for 5 hours, and then the temperature is further increased to 900°C at a rate of 5°C per minute, and then cooled to room temperature for 15 hours to obtain the product.

[0059] NeNi 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 Preparation (Ni high)

[0060] Raw material: Na 2 CO 3 , Ni-MOFs, MnO 2 , CuO, Fe2 O 3 、TiO 2 ,MgO

[0061] Preparation method: Similar to the above-mentioned preparation method of general high, NiO is replaced by Ni-MOFs as the nickel source precursor. According to the stoichiometric ratio, weigh the above-prepared Ni-MOFs as the nickel source, 0.334g Na 2 CO 3 (5% excess to make up for the lack of sodium in high temperature calcination), 0.261g MnO 2 , 0.0795g CuO, 0.0798g Fe 2 O 3 , 0.0798 g TiO 2 , 0.04g MgO. After the above raw materials are fully ground in an agate mortar for 1 hour, the gray powder is dispersed into a porcelain boat, and the porcelain boat is placed in a simple position in a tube furnace, and the temperature is increased to 500°C at a rate of 5°C per minute for 5 hours, and then the temperature is further increased to 900°C at a rate of 5°C per minute, and then cooled to room temperature for 15 hours to obtain the product.

[0062] NeNi 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 Preparation (Ni / Mn high)

[0063] Raw material: Na 2 CO 3 , Ni / Mn-MOFs, CuO, Fe 2 O 3 , TiO 2 ,MgO

[0064] Preparation method: According to the stoichiometric ratio, the Ni / Mn-MOFs prepared above were weighed as nickel source and manganese source precursors, 0.334 g Na 2 CO 3 (5% excess to make up for the lack of sodium in high temperature calcination), 0.0795g CuO, 0.0798g Fe 2 O 3 , 0.0798gTiO 2 , 0.04g MgO. After the above raw materials are fully ground in an agate mortar for 1 hour, the gray powder is dispersed into a porcelain boat, and the porcelain boat is placed in a simple position in a tube furnace, and the temperature is increased to 500°C at a rate of 5°C per minute for 5 hours, and then the temperature is further increased to 900°C at a rate of 5°C per minute, and then cooled to room temperature for 15 hours to obtain the product.

[0065] Button battery assembly

[0066] 1. Preparation of pole piece

[0067] Raw materials: polyvinylidene fluoride (PVDF), N-methylpyrrolidone (NMP), carbon black (acetylene black), active materials

[0068] According to the ratio of 85% / active material, 10% PVDF, and 5% carbon black (acetylene black), the above three powders are ground evenly in a mortar. Then, a proper amount of NMP is slowly added (the powder forms a viscous paste), and after stirring, it is evenly coated on the copper foil with a film applicator. After the copper foil is vacuum dried at 80°C for 8 hours, it is cut into 14×14mm circular positive electrode sheets with a cutter.

[0069] 2. Battery assembly

[0070] Raw materials: pole piece with active material, sodium electrolyte (NaClO4), nickel foam (14×14 mm), lithium sheet (14×14 mm), separator (GF / D, 18×18 mm), argon gas, button cell positive and negative electrode shell (CR2025)

[0071] Place the electrode with active material into the battery shell, then put in the GF / D separator, slowly drip 100µL of electrolyte to make it completely soak the electrode, then put in the lithium sheet, nickel foam and battery shell in turn, and then use a tablet press to press the tablet at a pressure of 55Mpa for 10s.

[0072] NaNi synthesized by X-ray diffractometer entropy modulation and MOF precursors 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 and entropy-regulated ordinary NaNi 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O 2 The crystal structure and phase purity of Figure 1 As shown, all characteristic peaks of each sample are sharp and clear, consistent with the typical O3-type structure, and the space group is Rm 3, indicating that the samples have high purity and good crystallinity.

[0073] Figure 2The charge and discharge cycle diagram of three different materials shows that the discharge specific capacity of Ni high entropy material is significantly better than that of the other two materials. The first discharge specific capacity reaches 130 mAh / g at a current density of 0.1C, while that of ordinary high entropy material is 83 mAh / g. The capacity performance of bimetallic MOF-synthesized Ni / Mn high entropy material is the worst, with only 72 mAh / g.

[0074] Figure 3 The cycling specific capacity of ordinary high entropy material, Ni high entropy material and Ni / Mn high entropy material at 0.1C. It can be seen that the Ni high entropy material synthesized by metal Ni-MOF material has maintained a higher capacity than the other two materials in 100 cycles, with a capacity retention rate of 88%. The capacity retention rate of ordinary high entropy material is 85%, but the initial capacity is not high. The fastest decaying material is Ni / Mn high entropy material with a capacity retention rate of 50% after 100 cycles.

[0075] Figure 4 It can be seen that when the charge and discharge rate increases from small to large and then from large to small, the specific capacity of the Ni high material is relatively well preserved. In addition, by comparison, the reversible performance of the Ni high material after a high rate and then back to a low rate is better than that of the general high and Ni / Mn high materials.

[0076] Figure 5 It can be seen that the slope of the straight line of the Ni high material is larger than that of the other two materials, and the charge transfer resistance (Rct) corresponds to the semicircle in the high frequency region. It can be seen that the Ni high electrode material has a smaller internal resistance and good electrolyte contact performance.

[0077] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a sodium ion battery layered cathode material synthesized based on MOF high entropy strategy, characterized in that: The following steps are involved: A precursor is prepared based on a metal-organic framework, wherein the precursor comprises: Ni-MOFs; Mixing Ni-MOFs with Na2CO3, MnO2, CuO, Fe2O3, TiO2, and MgO to obtain a mixed precursor; The mixed precursor is subjected to high-temperature calcination to obtain a sodium ion battery layered positive electrode material; the high-temperature calcination conditions include: heating to 500° C. at a rate of 5° C. per minute, calcining for 5 hours, further heating to 900° C. at a rate of 5° C. per minute, calcining for 15 hours, and finally cooling to room temperature; The process of preparing Ni-MOFs includes: Prepare a first raw material, wherein the first raw material includes: Ni(NO3)2·6H2O, PTA and DMF; 0.4984 g of PTA was added to 15 ml of DMF at room temperature to obtain a first PTA solution; and 0.8724 g of Ni(NO3)2·6H2O was added to 10 ml of DMF to obtain a Ni(NO3)2·6H2O solution; After stirring the first PTA solution and the Ni(NO3)2·6H2O solution respectively, pour the stirred first PTA solution into the Ni(NO3)2·6H2O solution and stir to obtain a transparent cyan mixed solution; Pour the transparent cyan mixed solution into the inner lining of a reactor at 120° for reaction for 12 hours, and cool to room temperature to obtain a cooled mixed solution; The cooled mixed solution is centrifuged, and during the centrifugation, it is repeatedly washed and centrifuged three times with anhydrous ethanol, and the washed and centrifuged solution is dried to obtain Ni-MOFs; The mixed precursor is calcined at high temperature to obtain a sodium ion battery layered positive electrode material, wherein the sodium ion battery layered positive electrode material comprises: High Ni NaNi 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O2; Preparation of NaNi with high Ni content 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 The O2 process includes: Using the Ni-MOFs as a nickel source precursor; The nickel source precursor, 0.334 g of Na2CO3, 0.261 g of MnO2, 0.0795 g of CuO, 0.0798 g of Fe2O3, 0.0798 g of TiO2 and 0.04 g of MgO were placed in an agate mortar and ground to obtain a gray powder; The gray powder is placed in a porcelain boat, and the gray powder is calcined at high temperature to obtain NaNi with high Ni content. 0.3 Mn 0.3 Cu 0.1 Fe 0.1 Ti 0.1 Mg 0.1 O2.

Citation Information

Patent Citations

  • Ni-MOFs-based O3 type sodium ion battery positive electrode material and preparation method and application thereof

    CN118791056A